HUBUNGAN PENINGKATAN KADAR LDL KOLESTEROL PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT UMUM HAJI MEDAN - Zaim Anshari (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Introduction: The causes of ischemic stroke by the high level of ldl cholesterol is still uncertain or can not be confirmed yet. The researches regarding the correlation of the high level of ldl cholestrol on the ischemic stroke patients only in small numbers with inconsistent result. Purpose: to know the correlation of high level of idl cholestrol on ischemic stroke patients. Method: this research is an analytic research by using restrospective study method on ischemic stroke patients whom hospitalized in Haji Medan General Hospital period January to Maret 2019. The datas were taken from patient medical records. Those datas will be analyzed by using chi square test. Result: there were 40 subjects whom are in ages of 61-70 years old. There was no correlation of high level of ldl cholestrol on ischemic stroke patients (p=0.943) which means (p>0.05) H○ is unaccepted. Discussion: there is no correlation of high level of ldl cholestrol on ischenic stroke patients